The Detriment Element And The Reinterpretation Of The Equitable Estoppel Doctrine In Malaysia - Bulan, Ramy (Journal of Malaysian and Comparative Law, 1999)
"The time has come for this court to recognize that the doctrine of estoppel is a flexible principle by which justice is done according to the circumstances of the case. It is a doctrine of wide utility and has been resorted to in varying fact patterns to achieve justice. Indeed, the circumstances in which the doctrine may operate are endless."